An Analysis of the Effectiveness of Murabaha Contracts in Reducing Credit Risk of Indonesian Islamic Banks - Zumrotul Azizah (MALIA: Jurnal Ekonomi Islam, 2024)
This study evaluates the effectiveness of murabahah contracts as a credit risk mitigation strategy at Bank Syariah Indonesia (BSI). Adopting a qualitative descriptive-analytical methodology, the study integrates primary and secondary data to analyze the implementation of murabahah contracts in Islamic banking practices. The study findings show general alignment with Islamic principles, but also identify several operational constraints. Deficits in customers’ understanding of the Islamic principles underlying the murabahah contract, as well as potential disparities in interpretation between customers and bank officers, are factors that hinder the optimization of this financing instrument. Nevertheless, the study concludes that murabahah contracts have substantial potential to reduce credit risk, provided that there is structured and effective management. Therefore, it is recommended that BSI improve its Islamic financial education program for customers, conduct periodic and comprehensive evaluations of the implementation of murabahah contracts, and conduct more detailed quantitative analysis to measure its impact empirically. The implementation of these recommendations is expected to strengthen the role of murabahah contracts in supporting the stability and sustainable growth of BSI.